(untitled) (Journal of Organizational Psychology, 2021)
This paper examines corporate social responsibility. We present insights from a highly influential paper. Here are the highlights from this paper: Organizational change has become inevitable. Although modernity is characterized by change, humans struggle with change as the future becomes increasingly unpredictable. The extended disorder that has become the norm can cause a sense of loss as well as anxiety for individuals, organizations and society. Unrelieved stress becomes perpetual and will undeniably influence organizational change efforts negatively. Thus, the impact of fear, anxiety and stress at an individual and organizational level is accentuated. This study followed a qualitative research approach and adopted a grounded theory methodology. Negative emotions dominated the research data which further indicated that individuals find it difficult to engage with change in a meaningful manner as fear, anxiety and stress dominate. Thus, human reactions to change are discussed, as the organizational challenge seems to be how to find workable methods to reduce fear, anxiety and stress. Else it may become persistent, intense, chronic or recurring. Real-life stresses may then further hamper individual functioning. The researcher conceptualizes the anti-leader and anti-manager. These concepts depict the negative characteristics of leadership and management which invariably increase individuals’ fear, anxiety and stress levels. Emotions elicited by the anti-leader or anti-manager could potentially split, divide and fragment a workforce. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.